Development of high free fatty acid crude palm oil as a biodegradable electrical liquid insulator as an alternative to mineral oil-based insulators - Muhamad Mustangin; Bambang Purwantana; Chusnul Hidayat; Radi (Cleaner Engineering and Technology, 2024)
Mineral-based oil is now often used for transformer oil. Unfortunately, this kind of oil is harmful and unfriendly to the environment, necessitating the use of vegetable-based products that are both ecologically benign and biodegradable. With its properties, crude palm oil (CPO) might be a possibility for a vegetable-based insulator. Concerning it, the goal of this study was to create a method for converting CPO into an insulator that fulfilled IEC 62770 requirements. The researchers created a CPO-based insulator using degumming, filtration, distillation, and a vacuum drying technique in their work. At vacuum pressures ranging from 15% to 65% vacuum and temperatures ranging from 150 °C to 200 °C, 0.05% phosphoric acid, 5% bleaching earth, and 10% zeolite were used in the degumming process. The best measurement results showed that the values of breakdown voltage and kinematic viscosity of 60 kV and 12.7 cSt, respectively, met the requirements. The moisture content was higher than the required value, while the acid content was still relatively high, namely 1.4 mg KOH/g, thus requiring further treatment. After treatment using 2% KOH, the acidity became 0.01 mg KOH/g, and the moisture content was 176 ppm thus meeting the requirement. The color of the insulator produced was light yellow, bright, and clear. The best treatment parameter combination found was a pressure of 51.9% vacuum with a temperature of 168.7 °C. This research showed that the vacuum pressure had a significant effect on moisture, kinematic viscosity, and acidity, while temperature had a significant effect on breakdown voltage and acidity.